Interactions between Grape Maturity Indices and the Quality and Composition of Chenin blanc and Colom bar Wines from Different Localities - Ellis, L. P.; Van Rooyen, P. C.; Du Plessis, C. S. (South African Journal of Enology and Viticulture, 2017)
Three grape maturity indices viz. degrees Balling (0 B), total titratable acidity (TT A) and the 0 B.pH product of musts were compared regarding their ability to predict optimum quality for Chenin blanc and Colombar wines. Comprehensive analytical data from 168 musts and corresponding wines for the 1978, 1979 and 1980 vintages from the Stellenbosch, Robertson and Lutzville areas were accumulated, and subjected to principal component analysis using variables and variable ratios selected by correlation to quality weighting. These results indicated that the two cultivars differed appreciably with respect to the value of all three measured indices. From this study it was not possible to select a specific index to predict optimum maturity in all cases. Optimum values for each index differed according to geographic locality.